Weak Hands and Soft Mouths. Elements of a Scribal Identity in the New Kingdom - Ragazzoli, Chloé (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
In the New Kingdom scribes can be understood and described as a social world and a cultural milieu. Contemporary sources testify to a specific scribal literature written by scribes, about scribes and for scribes, with the Late Egyptian Miscellanies included. They let us glimpse the ideology of a subelite who redefine in their own terms emblems such as the hand, the fingers, the mouth, which are the organs for reading and writing, and the specific means for scribes to act on and in the world.